2012
DOI: 10.1590/s0006-87052012005000030
|View full text |Cite
|
Sign up to set email alerts
|

Influência da infestação de Diatraea saccharalis (Fabr.) sobre parâmetros tecnológicos da cana-de-açúcar

Abstract: A broca Diatraea saccharalis é uma das pragas mais importantes da cana-de-açúcar no Brasil, razão pela qual é relevante quantificar a interferência de seu ataque nos parâmetros tecnológicos dos colmos, utilizados como matéria-prima na indústria de açúcar e etanol. Assim, o objetivo do presente trabalho foi avaliar os efeitos da intensidade de infestação sobre os parâmetros tecnológicos, entre os quais fibra na cana e pol na cana, das cultivares IAC91-1099, IACSP93-3046 e IACSP95-5000. Para tanto, os colmos col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 1 publication
1
7
0
3
Order By: Relevance
“…Due to significant Brix reduction, there was a 34% sucrose reduction in the plant. Dinardo-Miranda et al (2012) observed that the infestation of the pest in sugarcane reduced sucrose and increased the amount of reduced sugars (fructose and glucose), also reported in the current study, in which the glucose content increased in bored stalks as compared to stalks from control treatment.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Due to significant Brix reduction, there was a 34% sucrose reduction in the plant. Dinardo-Miranda et al (2012) observed that the infestation of the pest in sugarcane reduced sucrose and increased the amount of reduced sugars (fructose and glucose), also reported in the current study, in which the glucose content increased in bored stalks as compared to stalks from control treatment.…”
Section: Discussionsupporting
confidence: 90%
“…In addition to quantitative effects, the borer also causes loss of juice quality in sugarcane (Dinardo-Miranda et al, 2012). This study reveals that high quality may be observed with the concentration of total soluble solids and sugars in the juice, influencing the production of ethanol.…”
Section: Discussionmentioning
confidence: 80%
“…On the other hand, CTC9 obtained the best technological parameters, with the highest averages of brix, fiber, purity and POL (Table 3). Therefore, it is possible to notice that the cultivars with lower mean values of TRS are also those with lower values of technological quality, brix, purity and POL; and higher levels of RS, characteristics also observed by DINARDO-MIRANDA et al (2012b, 2013. Sugarcane plants can response to injury and produce secondary compounds as phenols.…”
Section: Resultsmentioning
confidence: 83%
“…The injury instigated by the insects combined with the phytopathogenic microorganisms may cause even greater losses of yield. The pest attack decreases the sugar content (by inversion of the sucrose stored in the plant) and contaminates the broth, which hinders the fermentation (DINARDO-MIRANDA, 2008; DINARDO-MIRANDA et al, 2012b). Therefore, the sugarcane borer infestations can interfere with the quality of the raw material (sucrose content, soluble solids, purity, acidity of juice and fiber) and reduce the sugar production and quality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation